2022
DOI: 10.2147/ijgm.s349232
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Guideline on Management of Postoperative Delirium in Older People for Low Resource Setting: Systematic Review Article

Abstract: Background Postoperative delirium is the highest prevalence and life-threatening complication following geriatric surgery. The overall incidence rate varies from 5% to 52% of hospitalized surgical patients based on the type of surgery that often began in the postanesthesia care unit and continues up to 5 days post-surgery. Postoperative delirium manifests as a hypoactive, hyperactive and mixed subtype. The mechanism of delirium development is not clear, but it is accepted that delirium is a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…However, our study found that cohort studies are the main cited articles in this field, and there are a large number of systematic reviews or meta-analyses of cohort studies. In order to evaluate the assessment of delirium and predict its risk factors, a cohort study is a more appropriate method, which we think is the reason for the large number of articles cited in this type of article ( 22 , 23 ). There is only one non-clinically relevant article, which introduces a hypothetical model of delirium that suggests that drugs that restore microglial choline to control or directly inhibit neuroinflammation need clinical trials ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our study found that cohort studies are the main cited articles in this field, and there are a large number of systematic reviews or meta-analyses of cohort studies. In order to evaluate the assessment of delirium and predict its risk factors, a cohort study is a more appropriate method, which we think is the reason for the large number of articles cited in this type of article ( 22 , 23 ). There is only one non-clinically relevant article, which introduces a hypothetical model of delirium that suggests that drugs that restore microglial choline to control or directly inhibit neuroinflammation need clinical trials ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it comprises risk assessment and stratification, risk reduction, and early identification and management. Prevention is the most effective management of delirium [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Delirium is defined as an acute change in mental status that leads to disturbance of perception, thinking, memory, attention, emotional status, as well as sleep rhythm disorders and is most often reversible [1]. According to the American Psychiatric Association, the diagnosis of delirium can be made if the patient has a disorder of attention, a disorganized flow of thoughts, or an altered level of consciousness that develops over a short period of time and has a fluctuating course during the day [2].…”
Section: Introductionmentioning
confidence: 99%
“…It can develop in all age groups, but more often after a surgery performed in older patients, with an incidence rate of 5 -52%, depending on the general condition of the patient and the extent of the surgery. It usually occurs in the first five postoperative days [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation